Introduction to organometallics - Chikkali, S.H.; Netalkar, S. (Metal-catalyzed polymerization: fundamentals to applications, 2017)
Polymers are gigantic macromolecules that are constructed by linking together a large number of smaller molecules called monomers through the process of polymerization. Polymer chemistry has evolved from a primitive, pragmatic discipline in the early 1920s to a well-established academic course today. The early efforts by Hermann Staudinger laid the foundation of rational polymer science and today it is nearly well understood as any other contemporary science. The fundamentals of chemistry and physics of polymers are detailed in many text books and we refer the reader to dedicated main stream polymer science books. 1 Nevertheless, the subject is forging ahead and is conquering new territories, and understanding of these new frontiers is equally important.